Muslims perceptions of safe alcohol use: a qualitative study in the Gulf Council Cooperation countries - Samah Alageel; Noura Alomair (BMC, 2024)
Abstract Aim The purpose of this study was to explore Muslim's perceptions and views of raising awareness on safe alcohol use and counterfeit alcohol harms in Islamic countries. Subject and methods Qualitative semi-structured interviews with a purposive sample from the Gulf Council Cooperation (GCC) countries. The data were analysed using a reflexive thematic analysis method. Results Twenty-three participants took part in this study. We have identified five themes from the data, including perceptions on alcohol use in the GCC, community's openness to alcohol discussions, approaches to raising awareness on alcohol use, all forbidden is desirable, and legalisation is the solution. All participants acknowledged the existence of alcohol use in GCC communities and advocated for the need to raise public awareness about the harms of alcohol use. Opinions on approaches to raising awareness varied. Some participants suggested focusing awareness on the religious messages prohibiting alcohol use, emphasising that alcohol is harmful in any quantity. For some, raising awareness of safe alcohol consumption was viewed as accepting and encouraging alcohol use, which goes against Islamic religious beliefs. Some participants attributed alcohol misuse and the consumption of counterfeit alcohol to the ban on alcohol products in some GCC countries. Conclusions Muslims acknowledge the existence of alcohol use in Muslim communities, yet there is a hesitancy in raising awareness of safe alcohol use. Although challenging, there is a need to combine the public health perspective on safe alcohol use while providing messages that acknowledge the religious aspect.